2007
DOI: 10.1074/jbc.m606305200
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Localization of Type III-delivered Pseudomonas ExoS with Endosome Vesicles

Abstract: ExoS (453 amino acids) is a bi-functional type III cytotoxin produced by Pseudomonas aeruginosa. Residues 96 -219 include the Rho GTPase-activating protein (RhoGAP) domain, and residues 234 -453 include the 14-3-3-dependent ADPribosyltransferase domain. Earlier studies also identified an N-terminal domain (termed the membrane localization domain) that comprises residues 51-77 and includes a novel leucine-rich motif that targets ExoS to the perinuclear region of cultured cells. There is limited information on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 62 publications
3
39
0
Order By: Relevance
“…Dissociation of the plasma membrane from the actin cytoskeleton through ExoS ADPribosylation of ERM proteins (35,36) provides a mechanism for ExoS-mediated bleb formation. Also, once injected into a host cell, ExoS has been found to localize to both the plasma membrane and perinuclear regions, and ADP-r activity can interfere with trafficking and maturation of intracellular vesicles/endosomes by colocalizing and ADP-ribosylating Rab5, which is critical for endosome maturation (9,58). The uncoupling of Rab signaling may enable P. aeruginosa to evade trafficking to perinuclear vacuoles, which we previously showed display late endocytic markers when T3SS mutants traffic, while endowing P. aeruginosa with the capacity for intracellular replication.…”
Section: Discussionmentioning
confidence: 99%
“…Dissociation of the plasma membrane from the actin cytoskeleton through ExoS ADPribosylation of ERM proteins (35,36) provides a mechanism for ExoS-mediated bleb formation. Also, once injected into a host cell, ExoS has been found to localize to both the plasma membrane and perinuclear regions, and ADP-r activity can interfere with trafficking and maturation of intracellular vesicles/endosomes by colocalizing and ADP-ribosylating Rab5, which is critical for endosome maturation (9,58). The uncoupling of Rab signaling may enable P. aeruginosa to evade trafficking to perinuclear vacuoles, which we previously showed display late endocytic markers when T3SS mutants traffic, while endowing P. aeruginosa with the capacity for intracellular replication.…”
Section: Discussionmentioning
confidence: 99%
“…TPD52 also bound both ADRP and TIP47 in a yeast two-hybrid system, and TPD52-ADRP interactions were validated using GST pulldowns. TPD52 was previously identified as a binding partner of perilipin residues 1-240 in a yeast two-hybrid screen (Yamaguchi et al, 2006) and as a TIP47 co-immunoprecipitating protein (Zhang et al, 2007). This indicates that TPD52 might directly co-operate with PAT proteins, to promote either lipid droplet trafficking and/or lipid storage at the lipid droplet surface.…”
Section: Altered Lipid Droplet Distribution In Tpd52-expressing Versumentioning
confidence: 99%
“…By contrast, knockdown of the Caenorhabditis elegans TPD52 orthologue F13E6.1 significantly reduces lipid storage as assessed by a genome-wide screening study (Ashrafi et al, 2003), and expression microarray analyses have identified increases in TPD52 levels in mouse and human adipose tissue from obese versus lean subjects (Clement et al, 2004;Keller et al, 2008;Nadler et al, 2000). TPD52 was also identified as a perilipin-binding partner in a yeast two-hybrid screen (Yamaguchi et al, 2006), and TPD52 co-immunoprecipitated with TIP47 and other proteins (Zhang et al, 2007). These studies suggest the possible involvement of TPD52 in regulating lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…ADP-ribosylation of Ras disrupts Ras-Raf1 signaling in in vivo (Zhang, 2007;Ganesan, 1999). In vitro, ADP-ribosylated Ras:G12V showed 55±6% reduced affinity toward Rin1…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhang and others has recently showed Rab5 and ExoS co-localization in target cells in vivo (Zhang, Deng et al 2007).…”
Section: Mono-adp-ribosylation Is Demonstrated In Equation (1) and Pomentioning
confidence: 99%